2D Crystal–Based Fibers: Status and Challenges. Issue 39 (13th August 2019) - Meng, Si; Kong, Tiantian; Ma, Wujun; Wang, Huide; Zhang, Han
Abstract: 2D crystals are emerging new materials in multidisciplinary fields including condensed state physics, electronics, energy, environmental engineering, and biomedicine. To employ 2D crystals for practical applications, these nanoscale crystals need to be processed into macroscale materials, such as suspensions, fibers, films, and 3D macrostructures. Among these macromaterials, fibers are flexible, knittable, and easy to use, which can fully reflect the advantages of the structure and properties of 2D crystals. Therefore, the fabrication and application of 2D crystal–based fibers is of great importance for expanding the impact of 2D crystals. In this Review, 2D crystals that are successfully prepared are overviewed based on their composition of elements. Subsequently, methods for preparing 2D crystals, 2D crystals dispersions, and 2D crystal–based fibers are systematically introduced. Then, the applications of 2D crystal–based fibers, such as flexible electronic devices, high‐efficiency catalysis, and adsorption, are also discussed. Finally, the status‐of‐quo, perspectives, and future challenges of 2D crystal–based fibers are summarized. This Review provides directions and guidelines for developing new 2D crystal–based fibers and exploring their potentials in the fields of smart wearable devices. Abstract : 2D crystal–based fibers are flexible and knittable, and they have great potential for smart wearables. A review of the research status of 2D crystal–based fibers and a summary of their preparation methods are presented. This Review is helpful for developing new varieties of 2D crystal–based fibers and realizing their applications such as wearable electronics.